Practical Applications in Radiography Education. - Spence, Brian (Radiologic Technology)
This article describes practical and innovative approaches in radiography education, including active learning strategies, technological tools such as virtual anatomical models and clinical simulators, and reflective writing exercises. It also discusses ways to foster professionalism and lifelong learning in radiography students.